Do all roads lead to the Rome? The glycation perspective!. (April 2018) - Ahmad, Saheem; Akhter, Firoz; Shahab, Uzma; Rafi, Zeeshan; Khan, Mohd. Sajid; Nabi, Rabia; Khan, Mohd Salman; Ahmad, Khurshid; Ashraf, Jalaluddin Mohammad; Moinuddin,
Abstract: Oxidative, carbonyl, and glycative stress have gained substantial attention recently for their alleged influence on cancer progression. Oxidative stress can trigger variable transcription factors, such as nuclear factor erythroid - 2-related factor (Nrf2), nuclear factor kappa B (NF-κB), protein - 53 (p - 53), activating protein - 1 (AP - 1), hypoxia-inducible factor - 1α (HIF - 1α), β-catenin/Wnt and peroxisome proliferator-activated receptor-γ (PPAR-γ). Activated transcription factors can lead to approximately 500 different alterations in gene expression, and can alter expression patterns of inflammatory cytokines, growth factors, regulatory cell cycle molecules, and anti-inflammatory molecules. These alterations of gene expression can induce a normal cell to become a tumor cell. Glycative stress resulting from advanced glycation end products (AGEs) and reactive dicarbonyls can significantly affect cancer progression. AGEs are fashioned from the multifaceted chemical reaction of reducing sugars with a compound containing an amino group. AGEs bind to and trigger the receptor for AGEs (RAGE) through AGE-RAGE interaction, which is a major modulator of inflammation allied tumors. Dicarbonyls like, GO (glyoxal), MG (methylglyoxal) and 3-DG (3-deoxyglucosone) fashioned throughout lipid peroxidation, glycolysis, and protein degradation are viewed as key precursors of AGEs. These dicarbonyls lead to the carbonyl stress in living organisms, possibly resulting in carbonyl impairment of proteins, carbohydrates, DNA, and lipoproteins. The damage caused by carbonyls results in numerous lesions, some of which are involved in cancer pathogenesis. In this review, the effects of oxidative, carbonyl and glycative stress on cancer initiation and progression are thoroughly discussed, including probable signaling pathways and the effects on tumorigenesis.